Evaluation of the genetic diversity of maize lines by microsatellite markers - Thu, Nguyễn Thị; Tuấn, Ngô Anh; Ngọc, Vũ Thị; Linh, Ngô Thị Thùy; Minh, Vương Huy; Thủy, Lê Thị Bích (Vietnam Journal of Biotechnology, 2018)
Recently, quantitative trait loci (QTLs) have been identified for resistance to ear rot. Techniques to ensure accurate phenotyping of Fusarium ear rot have been developed and validated. DNA marker technologies have matured and become economically feasible for some DNA marker assisted selection programs. Research and breeding efforts aimed at improving resistance to the Fusarium ear rot, identifying sources of resistance and characterizing the inheritance of ear rot. Resistance to Fusarium ear rot is under genetic control, but no complete resistance has been identified in maize. Once suitable sources of resistance have been identified, inheritance of resistance should be considered before selecting a breeding strategy, so evaluation of genetic diversity of maize lines is necessary for cross combination. Genetic diversity analysis of 71 inbred lines by 10 SSR markers detected 10 loci with a total of 42 alleles and average of 4.2 alleles per locus, the number of alleles on a locus varied from 3 to 6. Polymorphic Information Content (PIC) varied from 0.5783 to 0.8088, average of 0.6981. The Umc1196 marker revealed the highest polymorphism, the Umc1249 marker gave the lowest polymorphism. 71 inbred lines were divided into seven main groups. The genetic similarity among 71 lines ranged from 0.333 to 0.976. H3062 line maize had the lowest genetic similarity coefficient (0.333). The lowest genetic similarity coefficient was recorded in H3062 and H84 (0.333). Two lines H161 and KC161 had the highest genetic similarity coefficient (0.976). Almost maize lines had high genetic similarity coefficient showing the same similarity in genetic relationship